2021
DOI: 10.1186/s40959-021-00108-9
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic colorectal carcinoma to the right atrium: a case report and review of the literature

Abstract: Background Cardiac metastasis due to colon cancer is extraordinarily uncommon. Given the rarity of diagnosis, there is paucity of evidence and hence, no established guidelines for evaluation or clinical management strategy. Clinical presentation We present the case of a 59 year old male with a previously treated colonic carcinoma who presented with new onset exertional dyspnea. He was noted to be having a right atrial mass on an echocardiogram perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Surgical resection of the tumor has also been tried; Koizumi et al reported that although surgery is rarely recommended for treating metastatic cardiac tumors, surgical treatment could be effective in obstructive and solitary lesions to provide symptom relief and increase life expectancy [8]. Among case reports review of 31 patients, 14 patients underwent only surgical resection of the cardiac tumor, three underwent only chemotherapy, four had surgery followed by chemotherapy, nine received no treatment, and two were lost to follow-up [3]. Due to the extensive spread of primary cancer in our patient, she was planned for palliative chemotherapy with a combination of capecitabine and oxaliplatin for six cycles, followed by maintenance with oxaliplatin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical resection of the tumor has also been tried; Koizumi et al reported that although surgery is rarely recommended for treating metastatic cardiac tumors, surgical treatment could be effective in obstructive and solitary lesions to provide symptom relief and increase life expectancy [8]. Among case reports review of 31 patients, 14 patients underwent only surgical resection of the cardiac tumor, three underwent only chemotherapy, four had surgery followed by chemotherapy, nine received no treatment, and two were lost to follow-up [3]. Due to the extensive spread of primary cancer in our patient, she was planned for palliative chemotherapy with a combination of capecitabine and oxaliplatin for six cycles, followed by maintenance with oxaliplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac metastases in CA are rare, with an incidence of 1.4-7.2%, according to autopsy studies [2]. To our knowledge, only 31 cases have been currently reported [3]. In this article, we discuss a case of CA with cardiac metastasis presenting with abdominal distention, obstipation, vomiting, melena, pallor, and irregular pulse.…”
Section: Introductionmentioning
confidence: 96%
“…The incidence of cardiac metastases varies from 2.3% to 18.3% 2 . Cardiac metastases result from primary tumour spread via haematogenous, lymphatic, direct invasion or intracavitary routes 3 . Primary tumours from the lung, including mesothelioma, breast and melanoma are most commonly associated with cardiac metastases 2 .…”
Section: Figmentioning
confidence: 99%
“…Primary tumours from the lung, including mesothelioma, breast and melanoma are most commonly associated with cardiac metastases 2 . By comparison, colorectal cancer rarely metastasizes to the heart with common sites of metastasis occurring in the liver, lung and peritoneum 3,4 …”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation